2010
DOI: 10.1002/ajmg.a.33766
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial deletion of 14q24.3‐q32.2 in a male patient with plagiocephaly, BPES features, developmental delay, and congenital heart defects

Abstract: Distal interstitial deletions of chromosome 14 involving the 14q24-q23.2 region are rare, and only been reported so far in 20 patients. Ten of these patients were analyzed both clinically and genetically. Here we present a de novo interstitial deletion of chromosome 14q24.3-q32.2 in a male patient with developmental delay, language impairment, plagiocephaly, BPES features (blepharophimosis, ptosis, epicanthus), and congenital heart defect. The deletion breakpoints were fine mapped using fluorescence in situ hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 12 publications
(23 reference statements)
1
11
0
Order By: Relevance
“…His distinctive facial findings were the only consistent findings from birth. There are some reports of the deletions of the long arm of chromosomal 14 that include the 14q24.3 region [Nielsen et al, 1978; Hreidarsson and Stamberg, 1983; Turleau et al, 1984; Yamamoto et al, 1986; Gorski et al, 1990; Karnitis et al, 1992; Ono et al, 1999; Cingoz et al, 2011]. Such previously reported chromosomal deletions could have been determined by conventional chromosomal analyses because the deletion sizes were much larger than that of the present patient.…”
Section: Discussionmentioning
confidence: 99%
“…His distinctive facial findings were the only consistent findings from birth. There are some reports of the deletions of the long arm of chromosomal 14 that include the 14q24.3 region [Nielsen et al, 1978; Hreidarsson and Stamberg, 1983; Turleau et al, 1984; Yamamoto et al, 1986; Gorski et al, 1990; Karnitis et al, 1992; Ono et al, 1999; Cingoz et al, 2011]. Such previously reported chromosomal deletions could have been determined by conventional chromosomal analyses because the deletion sizes were much larger than that of the present patient.…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that four patients who carried large deletions at 14q24.3-q32 that overlap NRXN3 and other genes also presented with facial dysmorphism. We observed that our proband and these four patients shared similar facial features, such as hypertelorism, flat nose bridge, long broad philtrum, auricle dysplasia and mild micrognathia [Schlade-Bartusiak et al, 2008; Cingoz et al, 2011; Riegel et al, 2014; Nicita et al, 2015]. Whether or not the NRXN3 deletion is responsible for facial dysmorphism requires further investigation.…”
Section: Discussionmentioning
confidence: 75%
“…We compared the phenotypes of all 23 cases carrying NRXN3 deletions and found that 9 patients (39%) had ASD, as the most consistent feature of individuals with NRXN3 deletion. Other features included language delay, social difficulties, intellectual disability, ADHD, temper tantrums, anxious, aggressive and obsessive behaviors [Schlade-Bartusiak et al, 2008; Cingoz et al, 2011; Vaags et al, 2012; Griswold et al, 2012; Riegel et al, 2014; Faheem et al, 2015; Nicita et al, 2015; https://decipher.sanger.ac.uk/]. Our proband’s maternal grandfather was diagnosed with schizophrenia, which was a rare phenotype in NRXN3 deletion patients.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients have in common craniofacial features, which were less severe in our case, and developmental delay. However, these characteristics were not constantly observed and some facial features, such as long philtrum, small mouth, hypertelorism or epicanthus were also described in patients with proximal and distal 14q interstitial deletion [22].…”
Section: Discussionmentioning
confidence: 98%
“…Most patients with this chromosomal abnormality share common clinical manifestations, such as microcephaly, micrognathia, broad nasal bridge, ear anomalies, hypotonia, developmental delay, congenital heart defects and agenesis of corpus callosum . So far, only 27 patients with proximal interstitial deletion of chromosome 14q11-q22 have been reported, including siblings and prenatally diagnosed cases [2][3][4][5][6][7][8][9][10][11][12][14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%